High-performance phase change material capsule by Janus particle. (June 2021) - Gui, H.; Li, Y.; Du, D.; Liang, F.; Yang, Z.
Abstract: A new method is proposed to fabricate high-performance phase change material capsules with high thermal storage capacity and increased thermal conductivity. The capsules are achieved by free radical polymerization against the example paraffin/water emulsions stabilized with Janus particles (JPs). It is key that the highly conductive Ag-contained JP adopt parallel lying at the emulsion interface, which is responsible for increasing the interfacial thermal conductivity. Thermal storage capacity can be retained over 90% with no paraffin leakage, which is stable after many cycles of heating and cooling. The high-performance phase change material capsules are promising in effective thermal management in the form of either powder or slurry. Graphical abstract: Image 1 Highlights: Ag nanoparticles contained Janus particle (Ag-JP) was used to stabilize a paraffin/water emulsion. Phase change material capsule was achieved by free radical polymerization against the emulsion. The capsule preserves a high thermal storage capacity of over 90% with no wax leakage after many cycles of heating and cooling. The interfacial thermal conductivity is greatly increased using the Ag-JP. The high-performance PCM capsules are promising in effective thermal management.